Plasma kisspeptin and ghrelin levels in puberty variant cases - Kurnaz, Erdal; Sen, Yasar; Aydin, Suleyman (Walter de Gruyter Gmbh, 2017)
Background: The aim of this study was to determine the serum levels of kisspeptin and ghrelin (GAH), as well as the relationship of these two peptides with each other in premature thelarche (PT) and premature adrenarche (PA) cases and to investigate the possibility of using these peptides as markers in the differentiation of puberty disorders. Methods: A PT group aged 1-8 years (n = 40), a PA group aged 1-9 years (n = 23, female/male = 20/3) and control groups consistent with each of the previous groups in terms of age and gender were created for the study. Kisspeptin and ghrelin levels were measured with ELISA methods from blood samples drawn while fasting in the morning. Results: When the PT group was compared with the controls, the plasma kisspeptin levels of the cases were significantly higher than the control group (165.47 +/- 15.45 pmol/L, 96.82 +/- 12.33 pmol/L, p = 0.005, respectively). Kisspeptin levels in the PA group did not show a difference with the control group (121.36 +/- 17.99 pmol/L, 95.52 +/- 11.54 pmol/L, p = 0.249, respectively). No significant difference could be found when GAH levels in the PT and PA groups were compared with controls. No significant correlation was found between kisspeptin and GAH levels in the PT and PA groups. Conclusions: Our results indicate that kisspeptin plays an important role in the PT, but GAH is not associated with puberty disorders.
Keywords: ghrelin (GAH); kisspeptin; premature adrenarche (PA); premature thelarche (PT)